More Baskets? Renewable Energy and Energy Security - Ulrike Lehr (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2009)
Energy security increasingly becomes an issue in the face of rising worldwide energy demand and dwindling resources. Threats to energy security are seen in political instabilities of resource exporting countries, decreasing reserves, geostrategic and geopolitical factors and the structure of the relevant energy markets in terms of market power, monopolies, cartels and trusts. The European Commission has issued two Green Papers on a strategy for the security of energy supply, supporting competitive international energy market (European Commission, 2000 and 2008). The large infrastructure and gas pipeline development project Nabucco through Turkey, Bulgaria, Romania, Hungary and Austria that has recently been launched is motivated by the assumed increase in energy security.
Keywords: Q4; 330; Energy; secruity; reneweable; baskets